Testosterone does not affect agrin cleavage in mobility‐limited older men despite improvement in physical function. (26th September 2017) - Gagliano‐Jucá, T.; Storer, T. W.; Pencina, K. M.; Travison, T. G.; Li, Z.; Huang, G.; Hettwer, S.; Dahinden, P.; Bhasin, S.; Basaria, S.
Summary: In a subset of men, sarcopenia and physical dysfunction occur due to destabilization of the neuromuscular junction (NMJ), which is manifested by elevated serum concentrations of C‐terminal agrin fragment (CAF). Testosterone administration improves physical function in some studies; however, its effects on serum circulating CAF concentrations remain unknown. Here we evaluate the effects of testosterone administration on circulating CAF levels in mobility‐limited men with low testosterone aged 65 or older participating in the Testosterone in Older Men with Mobility Limitations (TOM) Trial. We analyzed the difference in change in serum CAF levels between testosterone and placebo groups, as well as its association with muscle strength and physical function. Association of change in serum CAF levels with serum total (TT) and free testosterone (FT) was also evaluated. Men randomized to testosterone experienced significant improvement in muscle strength and physical function (assessed by loaded stair‐climbing power). However; testosterone administration was not associated with a reduction in serum CAF levels (effect size = −50.3 pm ; 95% CI = −162.1 to 61.5 pm ; p  = 0.374); there was no association between changes in CAF levels with changes in TT ( p  = 0.670) or FT ( p  = 0.747). There was no association between changes in serum CAF levels with improvement in either muscle strength or stair‐climbing power. In conclusion, testosterone treatment in mobility‐limited older men with low to low‐normal testosterone levels did not reduce serum CAF levels. Additionally, testosterone‐induced improvements in muscle strength and physical function were not associated with changes in serum CAF concentrations. These findings suggest that improvement in physical function with testosterone replacement in older men with mobility limitations and elevated CAF levels is mediated by mechanisms other than stabilization of the NMJ.